Model Order Reduction Volume 2: Snapshot-Based Methods and Algorithms - Benner, Peter; Schilders, Wil; Grivet-Talocia, Stefano; Quarteroni, Alfio; Rozza, Gianluigi; Miguel Silveira, Luís (Model Order Reduction, 2020)
An increasing complexity of models used to predict real-world systems leads to the need for algorithms to replace complex models with far simpler ones, while preserving the accuracy of the predictions. This two-volume handbook covers methods as well as applications. This second volume focuses on applications in engineering, biomedical engineering, computational physics and computer science.